Renal artery embolization for managing uncontrolled hypertension in a kidney transplant candidate - Alhamid, Naji; Alterky, Hani; Othman, Mohammad Imad (Avicenna Journal of Medicine, 2013)
We report a case of pre-operative bilateral renal artery embolization to control the resistant and malignant hypertension in a patient prepared for kidney transplantation. A 34-year-old man with end-stage renal disease as a result of the focal segmental glomerulosclerosis and uncontrolled hypertension that precluded the transplantation surgery and the patient′s post-transplant blood pressure and the renal function remained within normal limits following the transplant for 6 months of follow-up.
Keywords: Kidney transplant; malignant hypertension; renal artery embolization